Cannabis withdrawal syndrome: An important diagnostic consideration in adolescents presenting with disordered eating. Issue 2 (26th November 2013) - Chesney, Tyler; Matsos, Laura; Couturier, Jennifer; Johnson, Natasha
ABSTRACT Although previously thought to have no withdrawal symptoms, there is now convergent evidence for a cannabis withdrawal syndrome (CWS), criteria for its diagnosis, and evidence of its impact in the adolescent population. Cannabis withdrawal syndrome represents an important and under‐recognized consideration in adolescents with disordered eating. We describe three clinical cases of adolescents presenting to an eating disorders program with primary complaints of gastrointestinal symptoms, food avoidance, and associated weight loss. They did not meet the criteria for an eating disorder, but did fulfill the DSM‐5 criteria for CWS. This report emphasizes the importance of considering the impact of heavy cannabis use in adolescents presenting with gastrointestinal complaints, and eating disorder symptoms, including weight loss. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:219–223)